127k views
0 votes
Please help asap

Inverse of a Function

Please help asap Inverse of a Function-example-1

1 Answer

6 votes

Answer:


f^(-1) (x)=-(1)/(6)x+1

Explanation:

To find the inverse of a function in equation form, first I recommend changing the f(x) to a y:

y = -6x + 6

Next step is to switch the x and y:

x = -6y + 6

Now solve for the new y:

x - 6 = -6y and


-(1)/(6)x + 1=y

You can put the inverse notation back in for y like I did in the answer section above.

User Abbos Tajimov
by
7.6k points